Neuronal-type-specific epigenome editing to decrease SNCA expression: Implications for precision medicine in synucleinopathies - Zhiguo Sun; Boris Kantor; Ornit Chiba-Falek (Elsevier, 2024)
Overexpression of SNCA has been implicated in the pathogenesis of synucleinopathies, particularly Parkinson's disease (PD) and dementia with Lewy bodies (DLB). While PD and DLB share some clinical and pathological similarities, each disease presents distinct characteristics, including the primary affected brain region and neuronal type. We aimed to develop neuronal-type-specific SNCA-targeted epigenome therapies for synucleinopathies. The system is based on an all-in-one lentiviral vector comprised of CRISPR-dSaCas9 and guide RNA (gRNA) targeted at SNCA intron 1 fused with a synthetic repressor molecule of Krüppel-associated box (KRAB)/ methyl CpG binding protein 2 (MeCp2) transcription repression domain (TRD). To achieve neuronal-type specificity for dopaminergic and cholinergic neurons, the system was driven by tyrosine hydroxylase (TH) and choline acetyltransferase (ChAT) promoters, respectively. Delivering the system into human induced pluripotent stem cell (hiPSC)-derived dopaminergic and cholinergic neurons from a patient with the SNCA triplication resulted in efficient and neuronal-type-specific downregulation of SNCA-mRNA and protein. Furthermore, the reduction in SNCA levels by the gRNA-dSaCas9-repressor system rescued disease-related cellular phenotypes including Ser129-phophorylated α-synuclein, neuronal viability, and mitochondrial dysfunction. We established a novel neuronal-type-specific SNCA-targeted epigenome therapy and provided in vitro proof of concept using human-based disease models. Our results support the therapeutic potential of our system for PD and DLB and provide the foundation for further preclinical studies in animal models toward investigational new drug (IND) enablement and clinical trials.